2016
DOI: 10.1371/journal.pone.0148699
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Hemogram Parameters for the Non-Sepsis Systemic Inflammatory Response Syndrome and Sepsis: What Do They Mean?

Abstract: ObjectivesSepsis is one of the most common reasons of increased mortality and morbidity in the intensive care unit. The changes in CRP levels and hemogram parameters and their combinations may help to distinguish sepsis from non-sepsis SIRS. The aim of this study is to investigate the CRP and hemogram parameters as an indicator of sepsis.MethodsA total of 2777 patients admitted to the ICU of two centers between 2006–2013 were evaluated retrospectively. The patients were diagnosed as SIRS (-), non-sepsis SIRS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…The results from the present study suggest that APACHE II performed best in discriminating HAP with noninfection status as a single indicator (Figure 2,3). It has been proved to be a valuable marker to predict mortality in septic patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study suggest that APACHE II performed best in discriminating HAP with noninfection status as a single indicator (Figure 2,3). It has been proved to be a valuable marker to predict mortality in septic patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…By the time a patient develops signs of an organ dysfunction or systemic inflammation it is often unclear whether these conditions are related to an infection or not [2,[14][15][16]. An infection-specific occurrence would therefore be essential for a reliable sepsis criterion [51].…”
Section: Infection-specific Occurrence Of Sepsis Criteriamentioning
confidence: 99%
“…In clinical practice not only the differentiation between 'uncomplicated infection' and sepsis is challenging. Additionally, by the time a patient develops signs of organ dysfunction or systemic inflammation it is often unclear whether these conditions are related to an infection or not [2,[14][15][16]. Ideal sepsis criteria should therefore not only differentiate between patients with sepsis and with uncomplicated infection, but also help to separate patients who are critically ill due to sepsis from those suffering from non-infectious conditions.…”
Section: Introductionmentioning
confidence: 99%
“…SIRS is defined clinically by the activation of the immune/inflammatory response, resulting in abnormal temperature or leukocyte count ( 4 ). Biomarkers have been identified that have the potential to diagnose, monitor, stratify and predict the outcome of these syndromes, for example, C-reactive protein and interleukin (IL)-18 elevation have been used as biomarkers indicating sepsis ( 5 , 6 ). However, many clinicians in the intensive care unit still face the challenge of diagnosing and accurately assessing the risk of outcome.…”
Section: Introductionmentioning
confidence: 99%